TATA LAKSANA PEMELIHARAAN AYAM BROILER PERIODE BROODING DI PT. JANUPUTRA FARM YOGYAKARTA - , MELAN NURMA SAPUTRI; , Dr. drh. M. Haryadi Wibowo, MP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
There are several periods of broilers raising system, one of which is the brooding period. The field practice activity regarding this period was carried out at Januputra farm in Mbokong, Sonoharjo, Seyegan, Sleman, Yogyakarta on 17 to 22 March 2014. This activity was aimed for obtaining data and experience regarding broiler raising in brooding period which is applied at Januputra farm. Data obtained by following the direct observation of work and at home, interview with the workers, then the results are compared with the literature. The brooding period in Januputra farm lasts for 14 days. The results show that the house leaching is carried out with the use of the high-pressures pray machine filled with water at all parts of the house. The leaching process with the use of detergent is not conducted. Disinfectionis conducted with the use of formalin by mixing 1 liter of formalin in 80 liters of water and spraying it all over the house. Decontamination of nuisance insects is not conducted. Liming is carried out by dissolving calcium oxide in the water, then evenly spreading it over the house. The house resting lasts for 3 days. The feeding, drinkers, blinds and pedestal litterare washed with the use of water and formaldehyde. The blinds are in the forms of tarps which are installed in two layers surrounding the house for the setting of temperature, lighting and ventilation with open and close systems according to the environment and the condition of the chickens. Rice husks are spread on the pedestal litter with the thickness of around 3-4 cm. Wet rice husks are stacked with new chaff. Chick guards are mounted by using zinc with a diameter of 5 m, and are widened everyday. The heater in the form of gasolek is installed as high as 1 m, and is lit 2 hours before the DOC come. There are 19 trayson the husks, and 6 automatic bell drinkers are installed intermittently as high as the chicken backstall when standing. Selecting and weighing the initial DOC was not carried out. The feed are in the forms of crumble RN-42 and B-11. The feed are given little by little but frequently as many as 5 times a day. The rest feed are spread in the husk area. Provision of drinking water is not limited. Sorbitol mixed in drinking water is then supplied to DOC when they come. Drinking places are cleaned every 2 days. Thermometer for temperature setting is not available. Chicken carcasses are dumped in the area of the raising. Astresvit is given everyday by mixing it into the drinking water. Vaccination is conducted 2 times. ND-IB combination vaccine is given at the age of 5 days through eye drops and subcutaneous injection, then Gumboro vaccine is given at the age of 12 days through drinking water. Based on the results of field practice activities which were then compared with the literature, it can be concluded that the broiler raising procedures in brooding period at Januputra farm is not good yet.